The effects of using augmented reality in rehabilitation and recovery exercise on patients’ outcomes and experiences: a systematic review - Modlin, Deiadra; Kuo, Yu-Tung (Frontiers in Virtual Reality, 2025)
Augmented reality, also known as AR, supplements reality by allowing the user to experience computer-generated graphics as though they appear in the real world. This literature review’s goal is to present a collection of data on AR-based exercise and rehabilitation applications. This literature review also aims to identify gaps within the existing research. The method of PRISMA was applied to systematic reviews for relevant articles published between 2017 and 2025. The databases include Academic Search Ultimate, British Library Serials, MEDLINE, and ProQuest Central. The results from the literature found that AR for rehabilitation could help patients physically and mentally and improve their motivation and engagement. Different types of AR tools were used to help with the rehabilitation of patients with health issues such as knee injuries or stroke. Questionnaires and medical tests were the common methods to gather data from the patients. AR rehabilitation technology may be able to bring a new form of human-computer interaction for patients.